Analisis Media Sosial Instagram Anies Baswedan sebagai Kampanye Politik Pilpres 2024 - Pamungkas, Rizqi Nandadita; Permadi, Didi; Florina, Ike Desi (JOPPAS: Journal of Public Policy and Administration Silampari, 2024)
This research aims to explore the role of Instagram in Anies Baswedan's political campaign ahead of the 2024 presidential election. The research method used is content analysis, research focuses on campaign messages and public interactions on the platform. The research results reflect positive support with high levels of community interaction, strengthening Anies' positive image. The campaign strategy, such as the tagline "AMEN" and visual symbolism, such as white clothes and the one finger symbol, succeeded in creating a strong identity. This research provides insight into how Instagram plays a role in shaping public opinion towards Anies Baswedan, highlighting the essentiality of social media in contemporary Indonesian politics. In conclusion, with Instagram as a key element, this research shows how this platform is an important means of political communication and the formation of the image of potential leaders. Keywords: Instagram, Campaign, Social Media, Personal Branding